A novel simulation method for power electronics: discrete state event driven method - Boyang Li; Zhengming Zhao; Yi Yang; Yicheng Zhu; Zhujun Yu (CES Transactions on Electrical Machines and Systems, 2017)
In the analysis of power electronics system, it is necessary to simulate ordinary differential equations (ODEs) with discontinuities and stiffness. However, there are many difficulties in using traditional discrete-time algorithms to solve such equations. Kofman and others presented the quantized state systems (QSS) algorithm in the discrete event system specification (DEVS) formalism. The discretization is applied to the state variables instead of time range in QSS. QSS is efficient to solve ODEs, but it is difficulty to be used when simulating actual power electronics systems with controller’s and other events. Based on the idea of this numerical algorithm and discrete event, a Discrete State Event Driven (DSED) simulation method is presented in this paper, which is fit for simulation of power electronics system. The method is developed to deal with non-linearity, stiffness and multi-time scale of power electronics systems. The DSED simulation method includes event definition, module seperation and modeling, event-driven mechanisms, numerical computation based on QSS, and some other operations. Simulation results verified the effectiveness and validity of the proposed method.